Peran mediasi ESG pada hubungan kepemilikan asing dan struktur modal: Moderasi likuiditas dan ukuran perusahaan - Oktrivina, Amelia; Nelyumna; Sailendra; Atikah, Salma; Sujana, Aaliyah Putri (Jurnal Akuntansi dan Manajemen, 2026)
This study aims to analyze the role of Environmental, Social, and Governance (ESG) as a mediating variable in the relationship between Foreign Ownership and Capital Structure, while considering Liquidity as a moderating variable and Firm Size as a control variable. A quantitative approach was employed using the Partial Least Squares–Structural Equation Modeling (PLS-SEM) method through the SmartPLS 4.0 application. The research sample consists of companies listed on the Indonesia Stock Exchange (IDX) during the 2020–2024 period that consistently reported ESG scores. The results indicate that foreign ownership has a positive influence on the implementation of ESG, while ESG strengthens the relationship between foreign ownership and capital structure. Thus, ESG serves as a partial mediating variable that links foreign ownership with corporate financing policy. Furthermore, liquidity is found to act as a moderating variable that enhances the relationship between foreign ownership and ESG. These findings highlight that foreign investors play an important role in encouraging the adoption of sustainability principles (ESG), which ultimately contributes to the efficiency of capital structure management. This research contributes to the development of sustainable finance literature and provides practical implications for corporate management and regulators to integrate ESG principles into financial policies and long-term business strategies.